ChemInform Abstract: Catalysis Inside Dendrimers. Issue 38 (3rd September 2015) - Astruc, Didier; Wang, Dong; Deraedt, Christophe; Liang, Liyuang; Ciganda, Roberto; Ruiz, Jaime
Abstract Review: [131 refs.